Advances in countercurrent chromatography for protein separations. (April 2012) - Mekaoui, Nazim; Faure, Karine; Berthod, Alain
Countercurrent chromatography (CCC) is a preparative purification technique working with biphasic liquid systems. One phase of the liquid system is selected to be the mobile phase, the other phase is the stationary phase, held still by centrifugal fields. Aqueous two-phase systems (ATPS) have demonstrated their use in biological purifications. This article reviews protein separations done by CCC using ATPS. The two types of CCC 'columns'' – hydrostatic and hydrodynamic instruments – are presented. All commercially available CCC equipments are listed. The hydrostatic CCC columns have an interesting potential to purify proteins working with ATPS aqueous liquid phases. The ATPS properties are briefly summarized, giving the polyethylene glycol 1000/dipotassium phosphate/water ternary mass phase diagram, along with the full chemical compositions of the two aqueous phases of important mixtures of this ATPS. Most published protein purifications were performed in academic laboratories. The highest throughput listed is 1.65 g/h of pure lyzozyme, obtained using a 5.5 l hydrostatic CCC column.